Microrganismos produtores de celulases: seleção de isolados de Trichoderma spp - Florencio, Camila (Universidade Federal de São Carlos, 2011)
The search for microorganism that produces cellulolytic enzymes is of the great importance in contributing to the viability of biological route for the production of cellulosic ethanol. Among filamentous fungi, the genus Trichoderma is characterized as a high enzyme producer. Given the growing demand for the development of processes that reduce the cost of cellulases had been proposed this work which aims to evaluate and select strains of filamentous fungi Trichoderma, available at Embrapa banks, capable of producing high concentrations of complex cellulolytic enzymes. The methodology developed in the project was divided in four steps until the final selection of the best strains. The first step of evaluation consisted in the observation of the growth of 78 pre-selected strains of Trichoderma from the degradation of microcrystalline cellulose, Avicel. The second step of selection, Congo red test, summarized in the determination of halo hydrolysis and the measurement of enzymatic index (diameter of halo hydrolysis. diameter halo colony-1) of each strain. The third stage was evaluated the strains with greater potential to produce cellulases in fermentation test tubes for the enzymes CMCase, Xylanase e FPAse. The last stage of evaluate and select of strains was solid-state fermentation (SSF). In the first step of selection, 49 strains showed the ability to metabolize the substrate microcrystalline cellulose, Avicel. The Congo red test, the second step, selected the ten best strains obtained with enzymatic indexes above 1.50, ranging from 1.51 to 1.90. In the process of fermentation in tubes were selected three strains with the better production of enzymes among the ten selected on Congo red test, T. harzianum CEN 139, T. harzianum CEN 155 and T. sp CG 104NH. For evaluation the enzymatic production in SSF was held initially a factorial experimental design to select the significant variables in the process. The variables studied were: inoculum concentration, moisture and proportion of sugarcane bagasse. After the CMCAse enzyme analysis was observed the proportion of sugarcane bagasse as a significant variable. From this result it was performed a central composite design for the improvement of fermentative parameters: the proportion of bagasse and moisture. The proportion of bagasse was significant and enzyme activity reached 11.16 UI.g-1 to CMCase. The process of SSF, among three tested strains, selected T. sp CG 104NH as the best producer of CMCase, Xylanase and FPase, with values of 25.93 UI.g-1, 67.17 UI.g-1 and 1.87 UI.g -1, respectively. The correlation coefficient between this process (SSF) and Congo red test was R2 = 0.97, 0.98 and 0.97 for the three enzymes studied, CMCase, Xylanase and FPase respectively. Therefore, it was possible to obtain a linear correlation between these two methodologies. The selection steps evaluated in this study were considered effective, quality selections proved quick selection of an extensive database of fungi. The linear correlation between the tests made with red Congo and SSF indicate that is possible to use the combination of qualitative and quantitative methods to assess the ability of cellulase production by filamentous fungi.
Keywords: Biotecnologia; Microbiologia; Microorganismos; Fermentação; Bagaço de cana; Trichoderma; Celulases; Fermentação em estado sólido; Microorganisms; Trichoderma; Cellulases; Solid-state fermentation; Sugarcane bagasse; OUTROS::QUIMICA INDUSTRIAL